Estudio sobre la comunicación organizacional en la efectividad académica con docentes de la Universidad Técnica De Babahoyo Extensión Quevedo, año 2021 - Solis Villacres, Dayamnis Marylin (2021)
The importance of carrying out a good relationship within an organization is of utmost importance so that the activities that it develops meet the objectives set from the beginning, in this case, it is a third-level educational institution in which there is an administrative staff whose good performance and organization will be reflected in the development and good reception that teachers have inside and outside the university grounds. The relationship that arises from the daily coexistence between teachers and students directly affects the effectiveness that their teachings have had on them, because the teacher is not only training a professional but also a great person; the vocational professor passionately passes on his knowledge and inspires those who listen. It is known to many that there is a group of academic leaders who make important decisions for the existence of the Technical University of Babahoyo and its extension in Quevedo, and that the well-being of its students is paramount for them, therefore their opinion always it is taken into account through evaluations through its web portal.